End of life of mosquito nets: searching for alternative uses through patent classification - Melani, Marco; Furferi, Rocco; Rotini, Federico; Barbieri, Luca (Frontiers in Manufacturing Technology, 2023)
The effects of global concerns such as climate change and environmental pollution must be considered also when dealing with the design or revamping of products or services nowadays. Already existing practices as 3R recovery approach and the Circular Economy approach, which aim to reduce waste and increase recycling, regeneration, and reusability, need to be applied during this process. This paper is embedded in this context, and it shows a study that was conducted within a manufacturing company on the possibility of reusing end of life mosquito nets, which are difficult to recycle, with the aim of reducing their environmental impact and create new business opportunities. To this goal, several supporting methods for new product applications identification have been evaluated from literature and the most suitable one has been selected. The method is based upon the identification of the product functions; then, with a series of patent searches, the cooperative patent classifications (CPCs) of the resulting patents are extracted to be used as external stimuli during the design process. The results obtained in terms of ideas generated are then shown at the end of the paper, suggesting the actual effectiveness of the method applied.